Effect of Interpersonal Communication Skills of Teachers in Teaching Teacher Motivation During the Pandemic COVID-19 - Nurul Hasanah; Muhazir Muhazir; Sari Wardani Simarmata; Azizah Batubara; Risma Dina (Journal Research of Social Science, Economics, and Management, 2022)
This study aims to determine the effect of interpersonal communication skills on teacher teaching motivation during the COVID-19 pandemic. This research was conducted at the Tunas Pelita Binjai Private Vocational School, TP 2021/2022. This research method uses a non-test technique in the form of a questionnaire (questionnaire). The sample of this study amounted to 50 teachers at the Tunas Pelita Binjai Private Vocational School. The sampling technique was done randomly. The results showed that from the simple regression test results obtained P-0.565 < 0.05, meaning that there was an influence between interpersonal communication on teacher teaching motivation during the COVID-19 pandemic at the Tunas Pelita Binjai Private Vocational School for the 2021/2022 Academic Year.